Design and Development of ‘Si Ebon’: A Cirebon Cultural Encyclopedia for Local Culture Revitalization in Early Childhood Education - Wahyudi, Ayu Vinlandari; Purnamasari, Yayu Mega; Hikmah, Fatihatul (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
Based on preliminary needs analysis, the availability of learning media that introduce local cultural knowledge to early childhood, particularly in the form of cultural encyclopedias, remains limited. As a result, children’s exposure to local cultural knowledge in formal learning environments is still relatively low, especially regarding Cirebon culture. This study aims to design, develop, and evaluate “Si Ebon,” a digital Cirebon cultural encyclopedia intended as a learning medium to support the revitalization of local culture in early childhood education (ECE). The study employed a development research approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The product was validated by media experts, subject matter experts, and cultural experts to ensure the appropriateness of the content, design, and cultural representation. The implementation involved teachers and early childhood students from several ECE institutions in Cirebon. Data were collected through questionnaires and observations and analyzed using descriptive quantitative techniques to determine the feasibility and effectiveness of the product. The results indicate that the “Si Ebon” digital encyclopedia is highly feasible and effective as a culturally responsive learning medium. Its use enhances children’s understanding of various elements of Cirebon culture, including local history, traditional arts, culinary heritage, traditions, and historical sites. This study contributes to the development of digital-based cultural learning media and highlights the potential of integrating local cultural content into early childhood education as a strategy for cultural revitalization.